Validity of documentary video learning media based on local content traditional musical instruments on sound waves - Hisbulloh Als Mustofa; Gunawan Gunawan; Kosim Kosim (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2021)
This study aims to determine the validity of the video documentary learning media based on local content of traditional musical instruments on sound wave material. This type of research is research and development. The development model used in this study is a 4D (Define, Design, Develop, and Disseminate) model developed by Thiagarajan. The validity of the product development in this study was tested for validity by 3 physics education expert lecturers and 3 physics teacher practitioners. The results of this study indicate that the documentary video learning media is feasible to proceed to the operational trial phase of learning. Based on the assessment by the validator, it has an average value of 93% with a very decent category, while from the results of student responses to this documentary video learning media through a limited trial, an average value of 89% is obtained with a very decent category.